A plugging agent suitable for CO2 gas channeling
By preparing a blocking agent containing acrylamide and acrylic acid, the problem of crude oil retention and system unstable in the process of CO2 Qi Ren in the CO2 oil -driven process is solved, and the effect of high -efficiency blocking CO2 gas channeling channel is achieved.
Patent Information
- Application Number
- CN202411319860.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-23
AI Technical Summary
During the CO2 oil flooding process, the CO2 gas traversal phenomenon causes crude oil to remain in the formation, reducing recovery rate and affecting the stability of the system operation. The existing gel-type sealing materials have poor injection properties in low permeability, low glue formation rate at high temperatures, and poor sealing effect.
Adopt a blocking agent including acrylamide, acrylic, nanopal polysaccharis, puffed soil, hydroxyetocellulose, leading agent, and surfactant, and preparation through ultrasonic dispersion and mixing The gel is to block the CO2 air.
The blocking agent is not easy to rupture in the acidic environment of CO2. It has high gel strength and long duration, which significantly improves the blocking effect, especially under the low -permeability layer and high temperature conditions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of oil production, and in particular to a method for 2 A plugging agent for gas channeling and a preparation method thereof. Background Art
[0002] CO 2 Gas drive oil production is the process of injecting CO into the oil layer. 2 Gas, CO 2 It has high solubility in both oil and water. When it is dissolved in crude oil in large quantities, it can expand the volume of crude oil, increase the elastic energy of the formation, reduce viscosity, and reduce the interfacial tension between oil and water. Under appropriate pressure, temperature and crude oil composition conditions, CO 2 It mixes with crude oil to form a miscible front, and then becomes a miscible liquid, forming a single liquid phase, thereby effectively displacing the formation crude oil to the production well. 2 The acid formed after dissolving in water can also play an acidifying role, which helps to further improve the recovery rate to increase the oil recovery rate of oil fields. 2 Gas has low viscosity and density, and is easy to flow in the oil layer, resulting in cross-flow. Secondly, factors such as reservoir heterogeneity, permeability, vertical heterogeneity of the reservoir, fracture development, sedimentary characteristics, and reservoir physical properties can also cause CO 2 Crossflow is prone to occur during oil displacement, resulting in CO 2 Breaking through the oil-bearing zone too early will cause a large amount of crude oil to remain in the formation, reducing the oil recovery rate; 2 Gas channeling can also cause abnormal fluctuations in gas pressure in the pipeline, affecting the stability of system operation, causing pipeline condensation, sealing packing leakage and other accidents. 2 During the oil recovery process, it is very important to take effective measures to prevent and control gas breakthrough.
[0003] The plugging materials used to prevent gas channeling mainly include gels, foams, organic amine salts, nanomaterials, etc. For gel plugging materials, when preparing the base fluid, the crosslinking agent and the polymer basically do not react. When the base fluid is injected into the formation, under the formation conditions, the initiator becomes active and begins to initiate a crosslinking polymerization reaction to generate gel to plug the CO 2 Gel plugging materials can effectively plug high permeability layers, but have poor injectability into low permeability layers, low gel strength, and low gelling rate at high temperatures, resulting in poor plugging effects. Summary of the invention
[0004] The object of the present invention is to provide a method suitable for CO 2 Gas channeling plugging agent can prevent and control CO2 Gas channeling, the gel strength is high and lasts for a long time after gelation. 2 In an acidic environment, the gel is not easy to break, has good stability and good blocking effect.
[0005] Another object of the present invention is to provide a method suitable for CO 2 A method for preparing a plugging agent for gas channeling, wherein the preparation method is simple, and the plugging agent prepared by the method has a high 2 The plugging effect in gas drive wells is good.
[0006] The present invention solves the technical problem by adopting the following technical solutions.
[0007] On the one hand, the embodiment of the present invention provides a method suitable for CO 2 The plugging agent for gas channeling includes the following raw materials, calculated by mass percentage: 5-10% acrylamide, 1-5% acrylic acid, 1-5% nano-chitosan, 0.5-1% bentonite, 1-5% hydroxyethyl cellulose, 0.1-0.5% initiator, 1-2% cross-linking agent, 0.1-0.5% surfactant, and the balance is water.
[0008] In some embodiments of the present invention, the following raw materials are used, calculated by mass percentage: 5% acrylamide, 1% acrylic acid, 1% nano-chitosan, 0.5% bentonite, 1% hydroxyethyl cellulose, 0.1% initiator, 2% cross-linking agent, 0.1% surfactant, and the balance is water.
[0009] In some embodiments of the present invention, the surfactant is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and betaine.
[0010] In some embodiments of the present invention, the cross-linking agent is one of ethylene glycol dimethacrylate and N,N-methylenebisacrylamide.
[0011] In some embodiments of the present invention, the initiator is one or more of potassium persulfate, sodium persulfate, and ammonium persulfate.
[0012] In some embodiments of the present invention, the particle size of nano-chitosan is 100-200 nm.
[0013] In some embodiments of the present invention, 1-2% of a reinforcing agent is further included by mass percentage.
[0014] In some embodiments of the present invention, the above-mentioned enhancer includes the following raw materials by weight: 10-20 parts of citric acid, 1-5 parts of calcium carbonate powder, 1-5 parts of porous silica, 5-10 parts of chitosan, 10-20 parts of ethanol aqueous solution, and 10-20 parts of sodium hydroxide solution.
[0015] In some embodiments of the present invention, the enhancer is prepared as follows: citric acid is added to an ethanol aqueous solution, stirred and dispersed evenly, chitosan is added, ultrasonic dispersion is performed for 30-60 minutes, calcium carbonate powder and porous silica powder are added, ultrasonic dispersion is performed for 30-60 minutes, and then the enhancer is added dropwise to a sodium hydroxide solution, allowed to stand for 10-20 hours, and filtered to obtain the enhancer.
[0016] First, citric acid and chitosan are dispersed in an ethanol solution to carboxylate some functional groups of the chitosan molecules. Then, calcium carbonate and porous silica are added and dispersed evenly before being dropped into an alkaline solution. In the alkaline solution, carboxylated chitosan is the shell, and calcium carbonate and silica are the core, forming a porous core-shell structure. The metal ions in the bentonite in the plugging agent are unstable. The citric acid groups on the surface of the core-shell structure can be complexed with metal ions through chelation to form a stable chelate, which is attached or adsorbed in the three-dimensional network structure of the gel. The connection strength between calcium carbonate and silica in the core-shell structure and the three-dimensional network structure is increased, thereby increasing the strength of the gel.
[0017] On the other hand, the embodiment of the present invention provides a method suitable for CO 2 The preparation method of the plugging agent for gas channeling comprises the following steps: adding the acrylamide, bentonite and surfactant into water, ultrasonically dispersing for 20-30 minutes, adding nano-chitosan and acrylic acid and stirring evenly, and then adding the remaining raw materials and stirring evenly.
[0018] When preparing the plugging agent of the present invention, acrylamide, bentonite and surfactant are first dispersed in water. Under the action of the surfactant, bentonite and acrylamide can be fully and evenly dispersed to reduce the viscosity of the system. Then, nano-chitosan and acrylic acid are added for dispersion, so that the main raw materials for forming the gel are evenly dispersed.
[0019] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:
[0020] The plugging agent provided by the present invention is injected into the CO 2 In gas drive wells, under the temperature environment of the oil well, the initiator is activated. Under the action of the initiator, acrylamide and acrylic acid undergo addition, cross-linking, polymerization and other reactions to generate macromolecules, which then form gels to block CO 2Gas channeling. During the polymerization process, nano-chitosan can be adsorbed on the surface of high molecular polymers, and the molecular chains of chitosan and ethyl cellulose contain hydroxyl groups, which can also participate in the addition polymerization reaction to form a three-dimensional network structure. The main component of bentonite is montmorillonite, which has a unique 2:1 crystal structure, consisting of two silicon-oxygen tetrahedrons sandwiching a layer of aluminum-oxygen octahedrons. When added to acrylamide and acrylic acid, it can participate in the addition polymerization reaction, combine with the polymer main chain, and embed into the network structure, thereby increasing the stability of the gel. Surfactants can reduce the viscosity of the plugging agent system, thereby improving the injectability of the plugging agent, especially the injectability of the low permeability layer. Furthermore, the hydroxyl groups in the chitosan and cellulose molecular chains in the raw materials can enhance the hydrophilicity of the plugging agent system, thereby reducing the initial viscosity of the plugging agent system; and after the reaction, the chitosan and cellulose molecular chains can be grafted and entangled with the main chain formed by acrylamide and acrylic acid, etc., to improve the viscosity and strength of the gel after gelation.
[0021] In summary, the plugging agent provided by the present invention can be used for CO 2 Prevention and control of CO in gas drive wells 2 The gel has high strength and good sealing effect after gas channeling. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0023] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to specific embodiments.
[0024] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0025] Example 1
[0026] Prepare the raw materials according to the following mass percentages:
[0027] Acrylamide 5%, acrylic acid 1%, nano-chitosan 1%, bentonite 1%, hydroxyethyl cellulose 1%, initiator (potassium persulfate) 0.1%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.1%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0028] The plugging agent of this embodiment is prepared as follows:
[0029] The acrylamide, bentonite and surfactant are added into water, and ultrasonically dispersed for 30 minutes, and then the nano-chitosan and acrylic acid are added and stirred evenly, and then the remaining raw materials are added and stirred evenly.
[0030] Example 2
[0031] Prepare the raw materials according to the following mass percentages:
[0032] Acrylamide 10%, acrylic acid 5%, nano-chitosan 5%, bentonite 0.5%, hydroxyethyl cellulose 5%, initiator (potassium persulfate) 0.4%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.5%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0033] The plugging agent of this embodiment is prepared as follows:
[0034] The acrylamide, bentonite and surfactant are added into water, and ultrasonically dispersed for 30 minutes, and then the nano-chitosan and acrylic acid are added and stirred evenly, and then the remaining raw materials are added and stirred evenly.
[0035] Example 3
[0036] Prepare the raw materials according to the following mass percentages:
[0037] Acrylamide 8%, acrylic acid 3%, nano-chitosan 3%, bentonite 0.8%, hydroxyethyl cellulose 3%, initiator (potassium persulfate) 0.5%, cross-linking agent (ethylene glycol dimethacrylate) 1.5%, surfactant (sodium dodecyl sulfate) 0.3%, the balance is water. The average particle size of nano-chitosan is 150nm.
[0038] The plugging agent of this embodiment is prepared as follows:
[0039] The acrylamide, bentonite and surfactant are added into water, and ultrasonically dispersed for 30 minutes, and then the nano-chitosan and acrylic acid are added and stirred evenly, and then the remaining raw materials are added and stirred evenly.
[0040] Example 4
[0041] Prepare the raw materials according to the following mass percentages:
[0042] Acrylamide 5%, acrylic acid 1%, nano-chitosan 3%, bentonite 1%, hydroxyethyl cellulose 1%, initiator (potassium persulfate) 0.1%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.1%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0043] The preparation method is the same as that of Example 1.
[0044] Example 5
[0045] Prepare the raw materials according to the following mass percentages:
[0046] Acrylamide 5%, acrylic acid 1%, nano-chitosan 5%, bentonite 1%, hydroxyethyl cellulose 1%, initiator (potassium persulfate) 0.1%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.1%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0047] The preparation method is the same as that of Example 1.
[0048] Example 6
[0049] Prepare the raw materials according to the following mass percentages:
[0050] Acrylamide 5%, acrylic acid 1%, nano-chitosan 5%, bentonite 0.8%, hydroxyethyl cellulose 1%, initiator (potassium persulfate) 0.1%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.1%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0051] The preparation method is the same as that of Example 1.
[0052] Example 7
[0053] Prepare the raw materials according to the following mass percentages:
[0054] Acrylamide 5%, acrylic acid 1%, nano-chitosan 5%, bentonite 0.5%, hydroxyethyl cellulose 1%, initiator (potassium persulfate) 0.1%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.1%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0055] The preparation method is the same as that of Example 1.
[0056] Example 8
[0057] Prepare the raw materials according to the following mass percentages:
[0058] Acrylamide 5%, acrylic acid 1%, nano-chitosan 5%, bentonite 0.5%, hydroxyethyl cellulose 1%, initiator (potassium persulfate) 0.1%, cross-linking agent (ethylene glycol dimethacrylate) 2%, surfactant (sodium dodecyl sulfate) 0.1%, reinforcing agent 1%, and the balance is water. The average particle size of nano-chitosan is 150nm.
[0059] The enhancer is prepared by the following method:
[0060] 10 parts by weight of citric acid are added to 20 parts by weight of ethanol aqueous solution (volume fraction is 80%), stirred and dispersed evenly, then 5 parts by weight of chitosan are added, ultrasonic dispersion is performed for 60 minutes, then 1 part by weight of calcium carbonate powder and 1 part by weight of porous silica powder are added, ultrasonic dispersion is performed for 30 minutes, then the solution is added dropwise to 20 parts by weight of sodium hydroxide solution (5wt%), allowed to stand for 20 hours, filtered, and the enhancer is obtained.
[0061] The plugging agent of this example was prepared according to the preparation method of Example 1.
[0062] Example 9
[0063] The difference from Example 8 is that in this example, the mass fraction of the reinforcing agent is 1.5%.
[0064] Example 10
[0065] The difference from Example 8 is that in this example, the mass fraction of the reinforcing agent is 2%.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that in this example, nano-chitosan, bentonite and hydroxyethyl cellulose are not added, and the mass percentage of each raw material is as follows.
[0068] Acrylamide 5%, acrylic acid 1%, initiator 0.1%, cross-linking agent 2%, surfactant 0.1%, water 91.8%.
[0069] Comparative Example 2
[0070] The difference from Example 1 is that in this example, nano-chitosan and hydroxyethyl cellulose are not added, and the mass percentage of each raw material is as follows.
[0071] Acrylamide 5%, acrylic acid 1%, bentonite 1%, initiator 0.1%, cross-linking agent 2%, surfactant 0.1%, water 90.8%.
[0072] Comparative Example 3
[0073] The difference from Example 1 is that in this example, bentonite and hydroxyethyl cellulose are not added, and the mass percentage of each raw material is as follows.
[0074] Acrylamide 5%, acrylic acid 1%, nano-chitosan 1%, initiator 0.1%, cross-linking agent 2%, surfactant 0.1%, water 90.8%.
[0075] Experimental example
[0076] 1. Plugging agent viscosity test
[0077] The plugging agents of Examples 1-3, Examples 8-10 and Comparative Examples 1-3 were used as experimental objects to test the viscosity of the plugging agents. The specific test methods are as follows:
[0078] (1) Using a Brookfield DV-III rotational viscometer at room temperature, the initial viscosity of the plugging agent was tested;
[0079] (2) Place the plugging agent in a constant temperature oven at 90°C. After the reaction is completed, calculate the gelling time and test the viscosity after gelling.
[0080] The test results are shown in Table 1.
[0081] Table 1 Viscosity of each plugging agent
[0082]
[0083] Among them, in the above Table 1, the gelation time is judged by visual inspection of the code standard. When the gel reaches level I, rigid gel, and the surface of the gel does not deform when the glass bottle is turned over, it is considered to be gelled. It can be concluded from Table 1 that the plugging agent provided by the embodiment of the present invention has an initial viscosity of less than 10 mPa·s at room temperature, a low viscosity, and strong injectability. After gelation, the viscosity of the gel is high and the plugging effect is good. Compared with Comparative Examples 1-3, polyhydroxy raw materials: nano chitosan and hydroxyethyl cellulose are not added in the comparative examples, and the initial viscosity is large because nano chitosan and hydroxyethyl cellulose contain a large number of hydroxyl groups, which are hydrophilic and can reduce the viscosity of the plugging agent system. Secondly, the three-dimensional network structure of the gel in the comparative example does not contain the relevant molecular chains of chitosan and cellulose, and the coagulation degree after gelation is correspondingly reduced, and the plugging effect is not good.
[0084] In Examples 8-10, a reinforcing agent with a core-shell structure is added. After gelation, the reinforcing agent can be embedded in or attached to the three-dimensional network structure. The chitosan group can increase the viscosity of the gel and play a thickening role. Therefore, compared with Examples 1-3, the viscosity of Examples 8-10 after gelation increases.
[0085] 2. Gel strength test
[0086] The plugging agents of Examples 1-3, Examples 8-10 and Comparative Examples 1-3 were used as experimental objects. The plugging agents were respectively placed in a constant temperature oven at 90°C, 100°C and 110°C for 8 hours of reaction. The viscoelasticity of the gel after gelation was measured using an MCR301 interfacial rheometer. According to the standard SY / T6296-2013, <1Pa is a weak gel, 1Pa-10Pa is a medium-strength gel, and >10Pa is a strong gel. The results are shown in Table 2.
[0087] Table 2 Strength of each plugging agent after gelling
[0088]
[0089] It can be concluded from Table 2 that the strength of each plugging agent after gelation can reach the level of strong gel, but the plugging agent provided in the embodiment has a higher strength after gelation than the comparative example. The plugging agent of comparative example 1 does not contain nano-chitosan, bentonite and hydroxyethyl cellulose in its raw materials, and its gel is mainly a polymer of acrylamide and acrylic acid reaction, and its strength is relatively low. Comparative example 2 adds bentonite on the basis of comparative example 1. Bentonite can be used as a reinforcing agent and embedded in the mesh structure of the gel, thereby improving the strength of the gel. It can be seen from Table 2 that the strength of comparative example 2 is slightly higher than that of comparative example 1.
[0090] In Examples 8-10, a reinforcing agent is added on the basis of Example 1. The surface of the reinforcing agent with a core-shell structure is citric acid carboxyl chitosan, and its citric acid group can form a chelate with bentonite, thereby improving the bonding strength between the reinforcing agent and the gel network structure, and can improve the overall strength of the gel. Therefore, the gel strength of Examples 8-10 is greater than that of Examples 1-3.
[0091] 3. Simulated plugging experiment
[0092] Acidic brine was injected into the artificial micro-fracture sandstone core by a constant pressure and constant speed pump at an injection rate of 1 ml / min. After the pressure was stabilized, the core permeability was tested, and the artificial core with a permeability of 1-2 mD was selected as the experimental object; then the plugging agent in the above embodiment and comparative example was injected into the core, and after reacting in a constant temperature oven at 90°C for 8 hours, CO was injected. 2 The displacement experiment was carried out to determine its plugging efficiency, and the results are shown in Table 3.
[0093] Table 3 Plugging performance of each plugging agent
[0094]
[0095] It can be concluded from Table 3 that the plugging agent provided in the embodiment can achieve a plugging efficiency of more than 90% in the plugging experiment in the simulated low permeability core. The plugging agent provided in the comparative example has a lower viscosity and strength after gelling, and the corresponding plugging efficiency is also reduced, and its plugging effect is poor.
[0096] In summary, in the plugging agent provided by the embodiment of the present invention, acrylamide and acrylic acid undergo addition, cross-linking, polymerization and other reactions to generate macromolecules, and then form a gel to block CO 2 Gas channeling. During the polymerization process, nano-chitosan can be adsorbed on the surface of high molecular polymers, and the molecular chains of chitosan and ethyl cellulose contain hydroxyl groups, which can also participate in the addition polymerization reaction to form a three-dimensional network structure and improve the strength of the gel. Secondly, montmorillonite in bentonite can also be added to the addition polymerization reaction of acrylamide and acrylic acid, combined with the main polymer chain, and embedded in the network structure, thereby increasing the stability and strength of the gel.
[0097] The core-shell structure enhancer has a surface group that can form a chelate with the metal ions in the three-dimensional network structure, while the calcium carbonate and silicon dioxide inside are reinforcing particles. The synergistic effect between the inside and outside can significantly improve the gel strength. The surfactant can reduce the viscosity of the plugging agent system, thereby improving the injectability of the plugging agent, especially the injectability of the low permeability layer. This plugging agent can be used for CO 2 Prevention and control of CO in gas drive wells 2 The gel has high strength and high plugging efficiency after gas channeling.
[0098] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A plugging agent suitable for CO2 gas channeling, characterized in that: Calculated by mass percentage, it includes the following raw materials: Acrylamide 5-10%, acrylic acid 1-5%, nano-chitosan 1-5%, bentonite 0.5-1%, hydroxyethyl cellulose 1-5%, initiator 0.1-0.5%, cross-linking agent 1-2%, surfactant 0.1-0.5%, enhancer 1-2%, and the balance is water; The reinforcing agent comprises the following raw materials by weight: 10-20 parts of citric acid, 1-5 parts of calcium carbonate powder, 1-5 parts of porous silicon dioxide, 5-10 parts of chitosan, 10-20 parts of ethanol aqueous solution, and 10-20 parts of sodium hydroxide solution. The enhancer is prepared as follows: citric acid is added to an ethanol aqueous solution, stirred and dispersed evenly, chitosan is added, ultrasonic dispersion is performed for 30-60 minutes, calcium carbonate powder and porous silica powder are added, ultrasonic dispersion is performed for 30-60 minutes, and then the enhancer is added dropwise to a sodium hydroxide solution, allowed to stand for 10-20 hours, and filtered to obtain the enhancer; The preparation method of the plugging agent comprises: adding the acrylamide, bentonite and surfactant into water, ultrasonically dispersing for 20-30 minutes, then adding nano-chitosan and acrylic acid and stirring evenly, then adding the remaining raw materials and stirring evenly.
2. The plugging agent suitable for CO2 gas channeling according to claim 1, characterized in that: Calculated by mass percentage, the following raw materials: Acrylamide 5%, acrylic acid 1%, nano-chitosan 1%, bentonite 0.5%, hydroxyethyl cellulose 1%, initiator 0.1%, cross-linking agent 2%, surfactant 0.1%, enhancer 1%, and the balance is water.
3. The plugging agent suitable for CO2 gas channeling according to claim 1, characterized in that: The surfactant is one or more of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and betaine.
4. The plugging agent suitable for CO2 gas channeling according to claim 1, characterized in that: The cross-linking agent is one of ethylene glycol dimethacrylate and N,N-methylenebisacrylamide.
5. The plugging agent suitable for CO2 gas channeling according to claim 1, characterized in that: The particle size of the nano-chitosan is 100-200nm.
Citation Information
Patent Citations
CO2 gas channeling prevention plugging agent for high-temperature high-salinity oil reservoirs and preparation method of CO2 gas channeling prevention plugging agent
CN106188403A
Environment-friendly polymeric micro-nano material for drilling fluid and preparation method thereof
CN109468123A